Evaluasi Goal Oriented Evaluation Model terhadap Efektivitas Penerapan Aplikasi AICBT dalam Pembelajaran PAI di SMK Al Imron - Mahfida Inayati; Rahmawati Rahmawati; Maimun Maimun (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2024)
Evaluation of the goal-oriented evaluation model on the effectiveness of the application of AICBT application in learning Islamic religious education is an evaluation with continuous, consistent implementation, checking the extent of achievement of goals with the application of AICBT (Al-Imron Computer Based Test) Web-based application which is specialized in evaluating the PAI lesson process which has the aim of obtaining knowledge both in knowing, understanding, internalizing and deepening the value of PAI teaching towards students. This research uses a type of qualitative research through a qualitative descriptive approach. Data collection techniques in the form of non-participant observations, namely researchers make observations, unstructured interviews, and documentation with descriptive-analytical analysis techniques. The results of the goal-oriented evaluation model on the effectiveness of the application of AICBT application in learning Islamic religious education are very effective. Judging from the evaluation of PAI learning, SMK Al-Imron since implementing the AICBT application has improved very effectively and efficiently on the PAI learning evaluation process to be achieved. This is evidenced by statistical data from 2019 to 2023 today, both from the assessment of knowledge, skills, and attitudes, which have increased effectively (success in achieving goals) to the evaluation of PAI learning.